Photon-Regulated DNA-Enzymatic Nanostructures by Molecular Assembly - You, Mingxu (2011)
Future smart nanostructures will have to rely on molecular assembly for unique or advanced desired functions. For example, the evolved ribosome in nature is one example of functional self-assembly of nucleic acids and proteins employed in nature to perform specific tasks. Artificial self-assembled nanodevices have also been developed to mimic key biofunctions, and various nucleic acid- and protein-based functional nanoassemblies have been reported. However, functionally regulating these nanostructures is still a major challenge. Here we report a general approach to fine-tune the catalytic function of DNA-enzymatic nanosized assemblies by taking advantage of the trans-cis isomerization of azobenzene molecules. To the best of our knowledge, this is the first study to precisely modulate the structures and functions of an enzymatic assembly based on light-induced DNA scaffold switching. Via photocontrolled DNA conformational switching, the proximity of multiple enzyme catalytic centers can be adjusted, as well as the catalytic efficiency of cofactor-mediated DNAzymes. We expect that this approach will lead to the advancement of DNA-enzymatic functional nanostructures in future biomedical and analytical applications.